Efeito do MTA (Agregado de Trióxido Mineral) sobre a atividade de macrófagos peritoneais - Taia Maria Berto Rezende (2003)
Mineral trioxide aggregates (MTA) must be biocompatible since they are used as endodontic sealer in regions that are inflamed or infected. In addition, it must not interfere with macrophage activity. Recent studies have divided macrophages into to subtypes, according to their response to stimuli: M1 (activated by the production of IL-12) and M2 (alternatively activated in the absence of IL-12 production). In this study, the effect of two commercial brands of MTA (ProRoot, kind gift from Tulsa Dental, Ballaigues, Switzerland, and MTA-Ângelus, kind gift from Odonto-lógika, Londrina, Brasil) on macrophage activity were tested. Elicited peritoneal macrophages of the M1 (from C57BL/6 mice) and the M2 (from IL-12 gene knockout mice in the C57BL/6 background) were used. Viability, adherence, phagocytosis of Sacharomyces boulardii, production of ROIs when stimulated with zymosan, and the production of TNF, IL-12, IL-10 and NO triggered by Fusobacterium nucleatum, Peptostreptococcus anaerobious and IFN- were determined. The sealers did not interfere with any of the analyzed parameters. However M1 and M2 differed in several aspects: M2 macrophages did not survive as well as M1 in polypropilene tube cultures; ingested higher numbers of yeast cells; produced higher levels of IL-10 when stimulated with F. nucleatum; produced lower levels of ROIs. We conclude that the sealers do not inhibit a pro-inflammatory response by M1 or M2 macrophages and that the two types of macrophages respond differently to some stimuli.